The mediating role of service adequacy in the relationship between follow-up and evaluation and service quality "Case study on commercial banks – Sudan – Elobied" - Mohammed, Mostafa Adam; Abker, Adam Yagoub; Abdelaziz, Abdelaziz Hassan (Journal of Economic, Administrative and Legal Sciences, 2023)
This study aimed to identify the mediating role of service adequacy in the relationship between follow-up and evaluation and service quality in commercial banks operating in the state of North Kordofan (El-Obeid). The analytical descriptive quantitative method was used, and the study relied on the non-probability (soft) sample. The study model was built and hypotheses developed based on the literature of previous studies, and data was collected through a questionnaire, where 80 questionnaires were distributed and 75 were retrieved, with a response rate of 94%. To ensure the degree of reliability of the data, the Alpha- Cronbach test was used. The method of path analysis and structural equation modeling was used to test the hypotheses of the study, through the statistical package for social sciences (SPSS) program. The study’s results showed that a partially positive relationship between follow-up and evaluation and the quality of banking services. The results also indicated that a partially positive relationship between follow-up and evaluation and the adequacy of service. The results of the study also showed that adequacy mediates the relationship between follow-up and evaluation and the quality of banking services. The study recommended the need to pay attention to performance evaluation by relying on clear and objective criteria and foundations to help achieve the quality of services provided, and work to constantly increase the efficiency of banking services and review everything that has an impact on the low efficiency of service, in addition to preparing training programs on a regular and continuous basis to educate employees about quality. And to provide them with the necessary skills to raise the adequacy of the services provided, which will reflect positively on the quality of banking services, to carry out the continuous follow-up of the quality application processes in commercial banks.